Beginner's guide to cooking with spices - JOSEPH VEEBE ([Place of publication not identified] : [Publishers name not idntified], 2019)
Spices and herbs have numerous health benefits including anti-inflammatory, anti-oxidant, anti-cancer and anti-bacterial properties. Using spices and herbs in daily cooking is one of the healthiest and easiest lifestyle changes one can make with immense health benefits. Most commonly used spices are turmeric, chili, coriander, cumin, ginger, garlic, and black pepper. All of these spices are known to have antioxidant, anti-inflammatory and anti-cancer properties and thus eating a healthy dose of curry could be your answer to preventing cancer, delaying Alzheimer$1 (Bs and warding off many other diseases. Spices and herbs offer other benefits too such reduce pain, improve circulation, improve digestion and help prevent diabetes among others.s
Keywords: Guide; Cooking